Predictive modeling and socioeconomic determinants of diarrhea in children under five in the Amhara Region, Ethiopia - Kassaw, Abdulaziz Kebede; Alebachew Muluneh, Ayana; Assefa, Ebrahim Msaye; Yimer, Ali (Frontiers in Public Health, 2024)
Background: Diarrheal disease remains a major public health problem due to high morbidity and mortality, which can impose a tremendous burden in developing countries, including Ethiopia. There is a lack of literature on the use of machine learning approaches to predict important predictors of diarrhea in children under five years of age in Amhara Region, Ethiopia.The aim of this study was therefore to clarify these issues.Methods: This study data comes from the Ethiopian Population and Health Survey. We have applied machine learning ensemble classifier models such as: Random Forests, K-Nearest Neighbors, Decision Trees, Support Vector Machines, Gradient Boosting, and Naive Bayes Model to Predict the Determinants of Diarrhea in Children Under Five in Ethiopia. Finally, SHAP value analysis was performed to predict diarrhea.Result: Among the seven models used, the Random Forest algorithm showed the highest accuracy in predicting diarrheal disease with an accuracy rate of 81.03% and an area under the curve of 86.50%. Families with the richest wealth status (log odd of -0.04), children without a history of Acute Respiratory Infections(ARIs) (log odd of -0.08), mothers who did not have a job (log odd of -0.04), children aged between 23 and 36 months (log odd of -0.03), mothers with higher education (log odds ratio of -0.03), urban dwellers (log odd of -0.01), families using electricity as cooking material ( log odd of -0.12), children who had no wasting in children under five years of age living in the Amhara region of Ethiopia were among children under five years of age who had not taken medications for intestinal parasites compared to their peers ( log odd of -0.01) and had not taken any medication against intestinal parasites had a significant association with diarrheal diseases. Conclusion: We therefore recommend that the implementation of programs to reduce diarrhea in children under 5 years of age living in the Amhara region should focus on eliminating socioeconomic barriers that limit mothers' access to wealth, work environment, fuel for cooking food and education as well as children's access to nutrition and health.